Asymmetric capital-tax competition, unemployment and losses from capital market integration - Rüdiger Pethig; Frieder Kolleß (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2009)
In a multi-country general equilibrium economy with mobile capital and rigidwage unemployment, countries may differ in capital endowments, production technologies and rigid wages. Governments tax capital at the source to maximize national welfare. They account for tax base responses to their tax and take as given the world-market interest rate. We specify conditions under which - in contrast to free trade with undistorted labor markets - welfare declines and unemployment increases in some countries (i) when moving from autarky to trade without taxation and/or (ii) when moving from trade without taxation to tax competition.
Keywords: E24; H25; H87; J64; R13; F21; 330; capital taxation; asymmetric tax competition; rigid wages; unemployment; losses from trade; Kapitalertragsteuer; Steuerwettbewerb; Mehr-Länder-Modell; Allgemeines Gleichgewicht; Lohnrigidität; Arbeitslosigkeit; Außenhandelsliberalisierung; Kapitalmobilität; Außenhandelseffekt; Theorie